Self-esteem and health-related quality of life in ostomized patients - Ferreira,Emmanuelle da Cunha (2017)
ABSTRACT Objective: to assess self-esteem (SE) and health-related quality of life (HRQoL) in ostomized patients due to colorectal cancer. Method: cross sectional research with a quantitative approach. Three instruments were used for data collection: one instrument containing sociodemographic and clinical data, Rosenberg's Self-Esteem Scale, and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire. Results: SE and HRQoL were considered satisfactory. Significant statistical difference was found in the social function domain and marital status, ostomy duration, location, and time; global health scale and ostomy type; cognitive function and pain in the ostomy site. There was a correlation between self-esteem and all the functional scales and the global health scale. Conclusion: knowing SE and HRQoL levels, in addition to the variables that influence them, supports ostomized patients' care planning, rehabilitation, and social autonomy.